Two-component thermosensitive hydrogels: Phase separation affecting rheological behavior. (July 2017) - Abbadessa, Anna; Landín, Mariana; Oude Blenke, Erik; Hennink, Wim E.; Vermonden, Tina
Graphical abstract: Highlights: Polymer ratios determine extent of phase separation in PEG/pHPMAlac/HAMA hydrogels. Phase separation leads to hydrophilic domains dispersed in a more hydrophobic phase. Phase separation affects rheological properties in a controllable fashion. Mathematical models enabled a priori identification of hydrogels with desired properties. Hydrogel 3D printing was achieved with a formulation based on model prediction. Abstract: Extracellular matrices are mainly composed of a mixture of different biopolymers and therefore the use of two or more building blocks for the development of tissue-mimicking hydrogels is nowadays an attractive strategy in tissue-engineering. Multi-component hydrogel systems may undergo phase separation, which in turn can lead to new, unexpected material properties. The aim of this study was to understand the role of phase separation on the mechanical properties and 3D printability of hydrogels composed of triblock copolymers of polyethylene glycol (PEG) and methacrylated poly( N -(2-hydroxypropyl) methacrylamide-mono/dilactate) (pHPMAlac) blended with methacrylated hyaluronic acid (HAMA). To this end, hydrogels composed of different concentrations of PEG/pHPMAlac and HAMA, were analyzed for phase behavior and rheological properties. Subsequently, phase separation and rheological behavior as function of the two polymer concentrations were mathematically processed to generate a predictive model. Results showed that PEG/pHPMAlac/HAMA hydrogels were characterized by hydrophilic, HAMA-richer internal domains dispersed in a more hydrophobic continuous phase, composed of PEG/pHPMAlac, and that the volume fraction of the dispersed phase increased by increasing HAMA concentration. Storage modulus, yield stress and viscosity increased with increasing HAMA concentration for low/medium HAMA contents (≤0.75% w/w), while a further increase of HAMA resulted in a decrease of the mentioned properties. On the other hand, by increasing the concentration of PEG/pHPMAlac these rheological properties were enhanced. The generated models showed a good fitting with experimental data, and were used to identify an exemplary 3D printability window for PEG/pHPMAlac/HAMA hydrogels, which was verified by rheological characterization and preparation of 3D printed scaffolds. In conclusion, a clear relationship between phase separation and rheological behavior in these two-component hydrogels can be described by complex functions of the two polymer concentrations. The predictive model generated in this study can be used as a valid tool for the identification of hydrogel compositions with desired, selected characteristics.